The role of pH signalling in stomatal responses - Wood, J (1996)
The role of cytoplasmic pH in guard cell signal transduction was investigated in epidermal strips of Commelina communis. The cytoplasmic pH of guard cells was measured by dual excitation ratio confocal laser scanning microscopy. Large transient alkalinisations occurred for up to 20 minutes both during closure, in response to ABA and calcium, and opening in response to IAA and fusicoccin. Therefore the direction of the pH change does not determine the direction stomatal movement in Commelina communis in contrast to previous reports in Paphiopedilum tonsum. Furthermore, CO2 caused a slow acidification during stomatal closure, indicating that pore movements are not always associated with a transient cytoplasmic alkalinisation. The internal pH of guard cells was buffered by low concentrations of isobutyrate. Small reductions in stomatal closure in response to ABA and calcium were observed, however, responses to CO2, IAA and fusicoccin were unaltered. High levels of isobutyrate stimulated wide stomatal opening for all stimuli. Therefore manipulation of cytoplasmic pH only give limited support in the case of ABA and calcium that cytoplasmic pH changes are either necessary for or modulate stomatal movements. The observed pH changes may therefore be a consequence of the mechanism underlying pore movement rather than genuine cytoplasmic signals per se, A model is described based on strong ion and weak acid chemistry which predicts that the observed pH transients result from changes in the concentrations of chloride and malate which charge balance the potassium fluxes during stomatal movements. No suitable fluorescent indicator was found to measure pH in either the apoplast or vacuole. However the volume of the guard cell lumen, vacuole, nucleus and chloroplast were directly measured during stomatal movements and the cytoplasmic volume was calculated. These volumes were used to re-calculate compartmental pH and ion concentrations from previous reports.